Current Trends in Symmetric Polynomials with their Applications - Kim, Taekyun (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue presents research papers on various topics within many different branches of mathematics, applied mathematics, and mathematical physics. Each paper presents mathematical theories, methods, and their application based on current and recently developed symmetric polynomials. Also, each one aims to provide the full understanding of current research problems, theories, and applications on the chosen topics and includes the most recent advances made in the area of symmetric functions and polynomials.